PENGARUH IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT CLOUD CALL CENTER SEBAGAI STRATEGI DALAM MENINGKATKAN KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN - Ita Rifiani Permatasari; Tri Ramadani Arjo; Kartika Indah Permatasari (Jurnal Akuntansi Bisnis dan Humaniora, 2022)
Through the Cloud Call Center page, PT Telkom has a customer service that is aimed at providing services to customers. The quality of CRM Cloud Call center services needs to be improved to solve customer complaints. This research aims to increase the number of customer satisfaction and loyalty through communicative interactions between cloud call center systems and customers. Several tools are used to build automated machines as applications for conducting Cloud Call Center training connected to data based via a server. The methodology in this research is to use path analysis. The results of the study indicate that there is a direct influence between the CRM Cloud Call center service system on customer satisfaction and customer loyalty. The indirect effect shows that there is a significant positive relationship between the cloud call center service system and customer loyalty through customer satisfaction.